2017
DOI: 10.1016/j.cub.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Massive Protein Import into the Early-Evolutionary-Stage Photosynthetic Organelle of the Amoeba Paulinella chromatophora

Abstract: The endosymbiotic acquisition of mitochondria and plastids more than 1 Ga ago profoundly impacted eukaryote evolution. At the heart of understanding organelle evolution is the re-arrangement of the endosymbiont proteome into a host-controlled organellar proteome. However, early stages in this process as well as the timing of events that underlie organelle integration remain poorly understood. The amoeba Paulinella chromatophora contains cyanobacterium-derived photosynthetic organelles, termed "chromatophores,"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 55 publications
3
130
0
Order By: Relevance
“…P. chromatophora acquired a novel primary endosymbiotic organelle called "chromatophore" approximately 100 million years ago (Delaye et al 2016). Proteomic analysis of these chromatophores identified a large set of imported AMP-like peptides as well as chromatophore-imported proteins harboring common N-terminal sequences containing AMP-like motifs (Singer et al 2017). These findings thus provide an independent example of a third primary endosymbiosis that is accompanied by the evolution of an AMP-derived protein import process.…”
Section: Argument For a Common Origin Of Tps With A Class Of Ha-rampsmentioning
confidence: 99%
“…P. chromatophora acquired a novel primary endosymbiotic organelle called "chromatophore" approximately 100 million years ago (Delaye et al 2016). Proteomic analysis of these chromatophores identified a large set of imported AMP-like peptides as well as chromatophore-imported proteins harboring common N-terminal sequences containing AMP-like motifs (Singer et al 2017). These findings thus provide an independent example of a third primary endosymbiosis that is accompanied by the evolution of an AMP-derived protein import process.…”
Section: Argument For a Common Origin Of Tps With A Class Of Ha-rampsmentioning
confidence: 99%
“…However, based on the reduced number of chromatophore-derived genes in the nuclear genome, it seems that EGT may have been less important in the establishment of the chromatophore in P. chromatophora than HGT from other bacteria, as c.170 genes of bacterial origin encode proteins likely to be targeted to the chromatophore (Nowack et al, 2016). Interestingly, the largest contribution of identified chromatophore-targeted proteins derive from the ancestral host genetic repertoire (Singer et al, 2017), a similar pattern to the one observed in Archaeplastida proteomes (Qiu et al, 2013), suggesting that in both primary endosymbioses the host played a crucial role in mediating cyanobiont integration.…”
Section: New Phytologist Similarities Between Primary Endosymbioses Imentioning
confidence: 99%
“…A second primary symbiogenesis, involving a distinct cyanobacterial strain from the Synechococcus ‐ Prochloron clade, generated a single species of photosynthetic amoeba called Paulinella chromatophora . Since P. chromatophora is unique among amoebae and has not diversified into multiple species, this second primary symbiogenetic event appears to have occurred very recently in amoeba evolution…”
Section: Multiple Cell Fusions In the Evolution Of Photosynthetic Eukmentioning
confidence: 99%
“…31 A second primary symbiogenesis, involving a distinct cyanobacterial strain from the Synechococcus-Prochloron clade, generated a single species of photosynthetic amoeba called Paulinella chromatophora. 32 Since P. chromatophora is unique among amoebae and has not diversified into multiple species, this second primary symbiogenetic event appears to have occurred very recently in amoeba evolution. p Both red and green algae have participated in many secondary symbiogenesis events with unrelated eukaryotes that generated photosynthetic organisms with a more complex organelle structure, which also includes DNA from the algal nucleus.…”
Section: Multiple Cell Fusions In the Evolution Of Photosynthetic Eukmentioning
confidence: 99%